A SOCIO-PRAGMATIC ANALYSIS OF APOLOGY AND FORGIVENESS UTTERANCES IN TWILIGHT MOVIE MANUSCRIPTS - ISTARIYANDARI, OKTISA (2010)
This research aims at describing the kinds of apology and forgiveness utterances and the intentions of employing apology and forgiveness utterances. The objects to be analyzed are apology and forgiveness utterances in the forms of words, phrases, and sentences. The writer takes the data from Twilight movie manuscripts entitled Twilight and Twilight New Moon. The type of this research is descriptive qualitative. The data source of this research is Twilight movie manuscripts. The method of collecting data is documentation nad the step are reading, watching, signing, gathering and coding the data. The analysis of the intentions the writer uses pragmatic analysis especially speech act theory, there are locution, illocution and perlocution. While the analysis of the reason, the writer employes sociolinguistic analysis particularly Dell Hymes ethnography of communication using SPEAKING formula. The results of the research show that: 1) There are three kinds of expressive apology and forgiveness. They are 3,33% for condoling, 93,34% for regretting, and 3,33% for requesting of forgiveness. 2) There are eight types of the intentions. They are 3,33% impression, 26,67% guilty, 43,33% regret, 3,33% acceptance of blame, 6,67% request of forgiveness, 6,67% respect, 6,67% being afraid and 3,33% close relationship.